INTERCYZA W ŚWIETLE BADAŃ ANKIETOWYCH STUDENTÓW POLSKICH I AMERYKAŃSKICH - Kosek, Mirosław; Ciaś, Aleksandra (Zeszyty Prawnicze, 2016)
ANTENUPTIAL AGREEMENT IN THE LIGHT OF THE RESULTS OF SURVEYS CONDUCTED ON POLISH AND AMERICAN STUDENTS Summary Matrimonial regime issues are one of the areas of family law which are seldom researched. The aim of this article is to present the matrimonial agreement, known also as the antenuptial agreement, from a research perspective, thus trying to provide a minimum account to fill in the gaps in the Polish literature of the subject.The article is composed of two parts: first a theoretical discussion of the antenuptial agreement from the perspective of Polish and American legal norms. The second part presents the results of a survey conducted among students. The objective of the survey was to assess respondents’ knowledge concerning matrimonial agreements and their personal attitude to them. The results of the survey helped the author to draw many valuable conclusions and to indicate the areas of research that still need to be covered. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />